Application of Artificial Intelligence in Drones in the Mining Industry: A Case Study - Kaushal , Hitanshu; Bhatnagar , Anupam (Research Highlights in Science and Technology Vol. 9, 2023)
In this chapter, we are utilizing AI-powered drones for the analysis of agricultural land use in mining leases. Drones in mining have shown tremendous growth and have also added significant value to all mining projects. With better coordination, in-depth analysis, diminished expenses, and heightened workers' safety, the mining industry has found its savior. The automation of drone control, which includes the control of navigation and movement, has been made possible by the use of artificial intelligence (AI). Numerous techniques, such as GPS tracking, computer vision, and machine learning algorithms, can be used to implement this application. During the survey, data was captured using drone instruments within the mining lease and up to 100 meters from its boundary. The data was used to create 3-dimensional models of the mining lease. The survey area and flying path were created using KML in software applications, which allowed for precise planning and execution of the drone flights. Drones are crucial for land surveying and mapping due to their unique mix of spatial coverage and resolution. The Orthomosaic product may produce high precision georeferencing if several ground-control points were used. In conjunction with field observations, drones provide a prompt and precise means of recording land data and its use. A drone survey and mapping operation was conducted within a mining lease situated near the village of Kanthariya, in the Tehsil and District of Chittorgarh, covering an area of 64.75 hectares, for the analysis of agricultural land use in the mining lease. The use of artificial intelligence to automate the control of drones is an application of AI in the field of drone technology. This technology can improve the accuracy and efficiency of drone operations, including navigation and movement.